Disembarkation Options of Illegal Migrants Rescue at Sea - Hasjim Djalal (The Republic of Indonesia Defense University, 2015)
The issue of rescuing distress people at sea, is a very important issue for Indonesia, particularly because it is an archipelagic country situated between two oceans and two continents and it becomes a major route for migrants due to its various maritime straits and the ‘porous’ coastlines. These geographical factors have also exacerbated some of the problems, particularly of some undocumented migrants and refugees passing through Indonesia, either by land, sea, or by air. The flow of illegal migrants to or through Indonesia has increased in recent years, particularly from Afghanistan, Bangladesh, Myanmar, Iraq, Iran, Sri Lanka, and Pakistan, that require comprehensive solution, either domestically, bilaterally, or regionally.